Variation of the Alkaloid Content of Peumus Boldus (Boldo) - Tirapegui-Calquin, C (Elsevier B.V., 2018)
Eighteen alkaloids were detected in the bark, leaves, wood and roots of Peumus boldus, including traces of secoboldine, N-methylsecoboldine (boldine methine), glaucine and norreticuline, not reported previously as constituents of this species. Using appropriate standards, we quantified thirteen of them by UHPLC-MS/MS. Boldine was dominant in the bark, and laurolitsine in wood and roots. The alkaloid composition of the leaves, determined for 130 individually identified trees, classified by age and sex, was highly variable, where N-methyllaurotetanine, laurotetanine, coclaurine and in some cases isocorydine predominated, but not boldine. © 2018 Elsevier B.V.